KEMAMPUAN MASYARAKAT DALAM MENGORGANISIR MITIGASI BENCANA GEMBA BUMI DAN TSUNAMI DI KELURAHAN TORONIPA KECAMATAN SOROPIA KABUPATEN KONAWE - Hasddin; Osu Oheoputra Husen; Taufik Taufik; Alvian Ishak; Jusran Sahiruddin; Muh Julian (Amal Insani Foundation, 2023)
The Soropia region (including Toronipa) is a disaster-prone area and has a high level of risk. The potential for earthquake events in the future is very likely to occur, so mitigation efforts should be carried out to reduce risk and community preparedness efforts in facing (emergency response) earthquake and tsunami disasters. The initial stage was conducting socialization and assessing the ability of the community to organize earthquake and tsunami disaster mitigation activities in Toronipa Village, Soropiah District, Konawe Regency. The result is that there is a change in the mindset and attitude patterns of the people of Toronipa Village to prepare themselves according to the prevention and preparedness criteria. In order to help the community responsible for the earthquake and tsunami disaster, this activity is implemented into the provision of a geographic information system in the form of route maps and assembly points, as well as proper evacuation main points. However, it is necessary to provide disaster facilities and infrastructure in Toronipa Village to provide preparedness for earthquakes and tsunamis which are very likely to occur at any time.